O esporte, a torcida e o amor: o brand love de brasileiros a seus times - Corat, Pedro de Bragan??a (2016)
Fans of sports team gets excited, interacts with others fans, buys to show their belonginess on that social group. However not necessarily this actions means that the individual is really a fan, that celebrates victories and suffers on losses. What difference a fan of a well-wishing is the love to the team (adapted from brand love) and the level of identification. The research, so, intended, at first, to measure the brand love differences between Brazilians fans of national teams and of foreigner teams. Likewise, intended to understand the differences on team identification and purchase intention on these same groups. That distinction is necessary because some numbers shows that Brazilians interest in foreigner teams and diverse sports is growing, so the research wished to investigate if there are Brazilians really being fans of foreigner teams or if they are just enthusiasts. The theoretical concepts that sustained the study were brand love, team identification and purchase intention as a consequent of both. A confirmatory factorial analysis and a structural equation modeling were applied. Results showed that there are no differences between brand love and team identification on Brazilians fans of national teams and Brazilian fans of foreigner teams. The last group???s purchase intention was bigger, by the way.